Veterinary extension services in the integration program of cattle farming and oil palm in Target Area Concentration (TAC) - Man, Norsida; Siaw, Shin Yee; Yusuf, Munifah Siti Amira; Azizah, Siti (ResearchersLinks, 2024)
Malaysia’s huge ruminant sector drives expansion and livestock self-sufficiency. However, Malaysia struggles to increase meat production to meet rising demand and reduce import dependence. Malaysia has 22.2% self-sufficiency, 5.6kg large ruminant meat consumption per capita, and 78.1% import dependency. Other obstacles include a lack of development, awareness, labour, technology, livestock farm facilities, and incompatibility of some cattle breeds. The study analysed cattle breeders’ expectations of veterinary extension services under the Department of Veterinary Services (DVS) Target Area Concentration (TAC) livestock integration program. A cross-sectional study used a self-administered questionnaire, and 200 program breeders responded. Data collected was analysed using the SPSS software version 23.0. The survey found that respondents have positive views and high expectations of veterinary extension services, officers, and the DVS. The respondents agreed that veterinary extension is critical in cattle farming because farmers cannot increase their cattle production without assistance from the DVS. The study recommended that DVS focus more on cattle breeding integration by providing the latest information and knowledge, funds, regulating drug prices, regularly visiting farmers’ ranches, and identifying farmers’ needs and expectations as a roadmap for developing this sector to make it more appealing to join and a viable investment venture. © 2024 by the authors